No Country For ‘Bad’ Men: Volatile Citizenship and the Emerging Features Of Global Neo-colonial Penality - Tripković, Milena (The British journal of criminology, 2023)
The article examines instances of de jure and de facto denationalization that arise from (suspected) terrorism by analyzing penal outcomes for affected citizens. The article first exposes cases of de jure denationalization that confine citizens to global spaces and draws parallels with instances of de facto denationalization that deny repatriation from abroad. I then argue that both situations signal state’s avoidance of the duty to punish, deviate from conventional penal aspirations and engender volatile global penality. To support this argument, I explore three questions: (1) who punishes, (2) who is punished and (3) what the purpose of punishment is. I conclude by exposing the emerging features of global neo-colonial penality as they pertain to both its objects and objectives.